Analysis of the Effect of Digitalization on the Profitability of Telecommunication Companies in Indonesia - Loso Judijanto; Raymond Wahyudi; Rahadiyan Surya (West Science Business and Management, 2024)
This research investigates the relationship between digitalization components and the profitability of telecommunication companies in Indonesia through quantitative analysis employing survey methods. In the rapidly evolving landscape of the telecommunication industry, digitalization plays a pivotal role in shaping operational strategies and driving financial performance. The study employs a structured questionnaire administered to key stakeholders within Indonesian telecommunication firms, with statistical analysis techniques, including Structural Equation Modeling with Partial Least Squares (SEM-PLS), used to analyze the data. The findings reveal significant positive relationships between digitalization components—network infrastructure, digital services, customer experience, and operational efficiency—and profitability indicators. These results underscore the strategic importance of digital transformation initiatives in enhancing the profitability of telecommunication companies in Indonesia, providing valuable insights for industry practitioners, policymakers, and researchers.